Sistematização da tutela inibitória e o Código de Processo Civil de 2015 - Silva, Bruno Campos (2018)
The present study deals with the systematization of inhibitory tutelage and the Brazilian Code of Civil Procedure. For this purpose, it is essential that the contextualization of inhibitory tutelage in the legal system, as well as its structure and functionality within the civil procedural system be refined. It is necessary to revisit some key procedural institutes, especially the lawsuit (adopting the lawsuit as a guaranteeing principle) and the jurisdiction, in order to provide an effective protection of the rights of those under jurisdiction, threatened by illicit acts (those that are contrary to the legal system). The inhibitory tutelage (ex vi of article 497, single paragraph, Code of Civil Procedure (CPC)), a kind of preventive injunction, with a constitutional basis (ex vi of article 5, XXXV), consubstantiates in a true differentiated jurisdictional tutelage, arising from uncontested specialization of the procedure. The essential (rectius: assumption) requirement of effective inhibition is the threat (real, concrete, contemporary), which may integrate the minimum assumptions to the exercise of the right to action (action conditions) or merit depending on the cognition practiced by the State together with other relevant premises, namely: (i) the presence of a future illegal act; (ii) no need to demonstrate damage; and (iii) absence of subjective elements – willful misconduct or guilt. Thus, judicial pronouncements have been outlined, which should be duly substantiated (e.g., judgments, interlocutory decisions - see article 203, CPC) and the guarantee of effectiveness of tutelage (e.g. atypical executive measures of art. 139, IV, CPC, without disregarding that the legal state is bound to the legal system). Inhibitory tutelage has autonomy, ruled by the common procedure, and implies the imposition of doing, not doing, delivering the item or payment of amount, with the possibility of incidence of coercive measure (e.g. daily fine – astreinte (pecuniary penalty)) in case of noncompliance; therefore, the threat of breach of the obligation (i.e., threat of future default) is sufficient. In addition, we sought to establish the main characteristic traits (true attributes) of the inhibitory tutelage (preventive injunction) and those belonging to the precautionary and definitive injunction. This paper advocates the possibility of applying the norms contained in the procedural structure inherent to the provisional tutelages (ex vi of articles 294 to 311, CPC). In so doing, it obviously keeps the peculiarities of each intended tutelage, since much as the legislator has imparted a new characterization to the inhibitory tutelage with the CPC, this has been blandly exercised, what could harm its effective functionality. Moreover, we also saw the possibility of using the anticipated inhibitory tutelage, based on urgency or evidence. Likewise, it could be previously requested, depending on the procedural structure foreseen in art. 303, CPC. In addition there is the possibility of stabilizing (totally or partially) the effects of inhibitory tutelage (enforcement effects are anticipated), without implying in material res judicata. Finally, the present study addresses the question of the application of fungibility in the context of provisional tutelage, especially preventive tutelage